Monitoramento da água do solo em plantio de Eucalyptus spp. - Gelain, Neiva Somavilla (2012)
The growing demand for forest products has allowed the increase in areas planted forests in Brazil. Eucalyptus is a fast growing tree species and is cultivated on a large scale, but still is a subject that causes controversy about the effect on the dynamics of soil water where they are deployed. Therefore, this study aimed to monitor water use by Eucalyptus dunnii Maiden settlement under different population densities in sandy soil. The study was conducted from the installation of an experiment implemented with Eucalyptus dunnii Maiden in native grass, at spaced 3.50 X3, 50, 3.50 X1, 75, 1.75 X1, X0 75 and 1.75, 87 meters in an Alfisol (Red Yellow Podzolic). The experimental design was a complete randomized block with three replicates. To measure the soil moisture to field technique was used in the time domain reflectometry (TDR). Thus, we installed two units in the TDR-100 manufactured by Campbell. Probes with metal double rod 20 cm long were installed horizontally every 30 inches deep, by means of trenching 2.10 meter depth in each plot, comprising seven layers trench. Soil moisture was monitored continuously in the period november/2011 at may/2012. In addition, assessments were made dendrometrical as total height and DBH (1.30 m). These evaluations were performed at 36 and 42 months of age. In periods, the measures taken by TDR moisture was very sensitive to changes in water content of soil, mainly in the superficial layers of the soil. However, much of the monitoring period there were very few precipitation events, which resulted in measures of low soil water content will also result in stunted growth.